2021
DOI: 10.1109/tim.2020.3014753
|View full text |Cite
|
Sign up to set email alerts
|

Flame Boundary Measurement Using an Electrostatic Sensor Array

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Experimental results were found to be consistent with those from a proven flame imaging system, suggesting that the electrostatic sensor is capable of measuring the oscillation frequency of a burner flame and hence flame stability. More recently, a linear electrostatic sensor array has been used to measure the boundary of a gaseous flame[72]. The results from the sensor array are in close agreement with those from the same flame imaging system.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Experimental results were found to be consistent with those from a proven flame imaging system, suggesting that the electrostatic sensor is capable of measuring the oscillation frequency of a burner flame and hence flame stability. More recently, a linear electrostatic sensor array has been used to measure the boundary of a gaseous flame[72]. The results from the sensor array are in close agreement with those from the same flame imaging system.…”
supporting
confidence: 56%
“…Significant research has been undertaken on the use of active ion current probes for flame detection or monitoring where the electrodes are biased using an external voltage source [69], [70], [159]- [162]. However, limited research has been conducted to utilise passive electrostatic sensors to monitor the flame characteristics [71], [72]. Further development is required to assess the efficacy of electrostatic sensors for advanced flame monitoring in comparison with the ion current detection methods.…”
Section: F Further Development Of Current Applications and Possible mentioning
confidence: 99%
“…The induced signal from the isolated electrode placed around the flame is entirely due to electrostatic induction from the charged species and thus its amplitude is very small and negligible. The signal from the exposed electrode installed around the flame originates from charge transfer and its amplitude is mainly related to the distance from the flame boundary to the electrode [19]. Information about the density of charged species in the flame can only be acquired using an isolated electrostatic probe inserted into the flame.…”
Section: A Sensing Principlementioning
confidence: 99%
“…Previous studies based on a noncontact electrostatic sensor array [19,26] or the digital imaging system [21] have shown that a diffusion flame has a dominant frequency within a comparatively lower range and the frequency corresponding to the largest peak in the power spectrum is regarded as the measured oscillation frequency of the diffusion flame. A point to note is that the noncontact electrostatic sensor array or the digital imaging technique measures the fluctuations of the flame shape or brightness to characterize the flame oscillatory characteristics, whereas the developed electrostatic probe detects the variation in charge density in the flame.…”
Section: ) Spectral Analysesmentioning
confidence: 99%
“…Electrostatic sensors have clear advantages including the simplicity in structure, cost-effectiveness and applicability to various environments [8], which are divided into invasive and non-invasive sensors. The former needs to extend a probe into the flame [9], which will inevitably affect the stability and burning rates of the flame, and the electrostatic signals of the latter are closely related to the distance between the flame and the sensor [10]. Every method has its advantages and disadvantages, and the combination of multiple sensors will be a good way of the advanced monitoring of burner flames.…”
Section: Introductionmentioning
confidence: 99%